2022
DOI: 10.1002/acr.24891
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Professional Development in Rheumatology for Primary Care Clinicians: A Systematic Review

Abstract: Objective. To determine the quality of published rheumatology-focused continuing professional development (CPD) for primary care clinicians (PCCs) for improving the care of patients with rheumatic diseases.Methods. The authors conducted a systematic review of CPD focused on rheumatology topics for PCCs. A librarian systematically searched PubMed, Embase, Web of Science, ERIC, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Sinico. Studies were limited to those conducted in North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Education of healthcare professionals was another important approach advocated by many participants, in view of their delay in primary care and/or non‐rheumatology specialties. This suggests the lack of knowledge of ARDs among non‐rheumatologist healthcare professionals, due largely to the insufficient undergraduate and continuing medical education in rheumatology 30–32 . Education of medical students, primary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education of healthcare professionals was another important approach advocated by many participants, in view of their delay in primary care and/or non‐rheumatology specialties. This suggests the lack of knowledge of ARDs among non‐rheumatologist healthcare professionals, due largely to the insufficient undergraduate and continuing medical education in rheumatology 30–32 . Education of medical students, primary care.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the lack of knowledge of ARDs among non-rheumatologist healthcare professionals, due largely to the insufficient undergraduate and continuing medical education in rheumatology. [30][31][32] Education of medical students, primary care. and other non-rheumatologist healthcare professionals on the suggestive features of ARDs and the importance of early treatment could not only address the unmet need of misdiagnosis and delayed referral, 20,22,23,25,29,[33][34][35][36] but also facilitate a supportive environment for early help-seeking among patients who are already seeking medical attention for ARD associated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We used a standard instrument to evaluate the impact of our program, aligning with a recent systematic review of continuing professional development in rheumatology for PCPs, which identified program evaluation as an area for improvement. 42 In conclusion, we have developed a free online program that improves participants' confidence in their ability to care for patients with or at risk of painful KOA. Whether the impact on improvements in confidence translate into better patient outcomes is an important area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…We reached a broad group of learners, who were extremely positive about the program, would overwhelmingly recommend it to others, and endorsed plans to implement evidence‐based practices. We used a standard instrument to evaluate the impact of our program, aligning with a recent systematic review of continuing professional development in rheumatology for PCPs, which identified program evaluation as an area for improvement 42 …”
Section: Discussionmentioning
confidence: 99%
“…Courses and bootcamps utilizing interactive teaching modalities have been created to support PCPs in this need 12,13 ; however, these may be of moderate quality, based on metrics including increased rheumatology knowledge, change in clinical behaviors, and improved patient outcomes. 14 Through its Education Partner Program, the American College of Rheumatology (ACR) has prioritized content dissemination to PCPs, specialists, and APPs who take care of patients with rheumatic diseases. 15 Clinician educators are central to leading these initiatives aiming to expand the pool of providers who capably deliver care to patients with rheumatic disease (Figure 1).…”
Section: Spectrum Of Learnersmentioning
confidence: 99%